2018
DOI: 10.1371/journal.pone.0194254
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic nanosilver synthesized in Metarhizium robertsii waste mycelium extract – As a modulator of Candida albicans morphogenesis, membrane lipidome and biofilm

Abstract: Due to low efficacy of classic antimicrobial drugs, finding new active preparations attracts much attention. In this study an innovative, cost-effective and environmentally friendly method was applied to produce silver nanoparticles (AgNPs) using filamentous fungi Metarhizium robertsii biomass waste. It was shown that these NPs possess prominent antifungal effects against C. albicans, C. glabrata and C. parapsilosis reference strains. Further detailed studies were performed on C. albicans ATCC 90028. AgNPs kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 56 publications
1
49
0
1
Order By: Relevance
“…Our results showed that AgNPs/CG was more efficient at suppressing the adhesion and biofilm formation of C. albicans than plant extract or AgNPs alone. Similar to our finding, several other studies demonstrated the inhibitory effect of AgNPs on C. albicans biofilm formation [8,61,66]. In addition, AgNPs biosynthesized by Dodonaea viscosa and Hyptis suoveolens leaf extracts were shown to suppress the biofilm formation of Candida spp.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that AgNPs/CG was more efficient at suppressing the adhesion and biofilm formation of C. albicans than plant extract or AgNPs alone. Similar to our finding, several other studies demonstrated the inhibitory effect of AgNPs on C. albicans biofilm formation [8,61,66]. In addition, AgNPs biosynthesized by Dodonaea viscosa and Hyptis suoveolens leaf extracts were shown to suppress the biofilm formation of Candida spp.…”
Section: Discussionsupporting
confidence: 91%
“…Our data demonstrated the blocking of hyphal growth using AgNPs/CG. Similarly, several studies demonstrated the suppression of the C. albicans morphogenesis using AgNPs [6,8,53,61] in a mechanism that involved targeting the Ras-mediated signal transduction pathways in C. albicans through the downregulation of the expression of cell elongation gene (Ece1), hyphal inducer gene (Tec), and yeast to hyphal transition genes (Tup1 and Rfg1), which are key genes for the morphological transition [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Różalska et al 54 suggested that antibiofilm activity was due to the extremely easy binding and enhanced penetration of the AgNPs into the biofilm structure which disturb the lipidome of cell membranes. 54 Another possible mechanism of antibiofilm activity of AgNPs could be due to inhibition of yeast morphogenesis. Inhibition of blastospores and hyphae forms by AgNPs also lead to the suppression of biofilm formation in Candida.…”
Section: Visualization Of C Albicans Biofilm By Congo Red Agar and Clsmmentioning
confidence: 99%
“…Inhibition of blastospores and hyphae forms by AgNPs also lead to the suppression of biofilm formation in Candida. 54 Lara et al 55 reported that the antibiofilm effect of AgNPs was mainly due to the disruption of the cell wall and survival of both the yeast and the filamentous forms of the Candida spp.…”
Section: Visualization Of C Albicans Biofilm By Congo Red Agar and Clsmmentioning
confidence: 99%